DETECTOR FOR SUBMILLIMETER WAVELENGTH RANGE ON THE BASIS OF THE MAN-MADE MATERIALS - A. K. Esman; V. A. Potachits; G. L. Kuleshov; V. K. Zykov (Приборы и методы измерений)
The uncooled high-performance bolometric detector based on an array of planar resonant elements, located on the double-threaded spiral trajectory in a strictly geometrical order, with microand nanoscales is developed. It is shown that the proposed detector for submillimeter wavelength range can reach the reflection losses of –26,4 dB, the standing wave ratio of 1,1 and conversion efficiency of ~ 98 %.